Planos de mobilidade urbana: Instrumento efetivo da política pública de mobilidade? - Vicente Correia Lima Neto; Ernesto Pereira Galindo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The mobility plan is the main instrument of the mobility policy. According to the City's Statute, all cities with more than five hundred thousand inhabitants must develop their plans. Within the federal law no 12.587/2012, this legal obligation has changed. Nowadays, cities with more than twenty thousand inhabitants have to develop it. Despite that obligation, since 2001 only 13 of the 36 cities have developed their plans. This paper aims to evaluate the effectiveness of those instruments and the relationship between them and the federal investments. Also, some considerations are made, highlighting the challenge for the municipalities to deal with the subject.
Keywords: R42; R48; R49; 330; mobility plans; Urban Mobility National Policy; PAC Mobility